COVID-19 Pandemic and Law No. 6 Year 2018 regarding Health Quarantine - Widjaja, Gunawan (Journal of Indonesian Health Policy and Administration, 2020)
By late March, to anticipate the spreading of COVID-19 pandemic, the President of the Republic of Indonesia has issued several regulations. The Author has examined that the main laws that were used as the based for the issuance of those regulations are Law No.6 Year 2018 regarding Health Quarantine (the Health Quarantine Law). Therefore in order to handle COVID-19 pandemic, an understanding of the Law become a must. The aim of this research is to elaborate and explain the Health Quarantine Law to reduce the COVID-19 pandemic. This research is normative legal research. The research used secondary data, which consisted of primary legal sources and secondary legal sources. Data were collected through the "google scholar machine". Data obtained were analyzed using a qualitative approach. Findings and analysis proved that besides those newly issued regulations there were several measures and acts that should be taken to handle the COVID-19 pandemic in Indonesia. The Author suggests that the Central Government shall take the necessary steps as soon as possible.